Immunosuppressive properties of Actinobacillus actinomycetemcomitans leukotoxin. - Rabie, G (1988)
Actinobacillus actinomycetemcomitans produces a leukotoxin that kills human polymorphonuclear cells (PMNs) and monocytes but not lymphocytes. In this study, we examined A. actinomycetemcomitans leukotoxin for its ability to alter human peripheral blood lymphocyte (HPBL) responsiveness. After a 90-min exposure to the leukotoxin, all monocytes were killed and HPBL responsiveness to mitogens and antigens was significantly inhibited. The ability of the leukotoxin to inhibit HPBL responses was not surprising, since monocytes and macrophages are required for many lymphocyte functions. However, we were unable to totally restore HPBL responsiveness when adherent autologous monocytes were added back to cultures of leukotoxin-treated lymphocytes. These studies demonstrate that A. actinomycetemcomitans leukotoxin may also exert nonlethal effects directly on lymphocytes. Furthermore, impaired lymphocyte function did not appear to be the result of indirect effects of products released by dying monocytes. Although it is not clear how A. actinomycetemcomitans acts to cause disease, several investigators have proposed that impaired host defenses may play a pivotal role. Several studies have demonstrated defects in PMN, monocyte, and lymphocyte function in patients with periodontal disease. These findings, along with the data presented in this paper, support the hypothesis that patients who harbor A. actinomycetemcomitans could suffer from local or systemic immune suppression. The effects of this suppression may be to enhance the pathogenicity of A. actinomycetemcomitans itself or that of some other opportunistic organism.